PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN NASABAH, DAN CITRA PERUSAHAAN TERHADAP TINGKAT KEPUASAN NASABAH PADA PT BIMA FINANCE MEDAN - Rizky Sanjaya; feby Milanie; M. Isa Indrawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research was conducted to know how the Influence of Service Quality, Trust, and Company Image on Customer Satisfaction at PT Bima Finance Medan. The population in this research were all customers of PT Bima Finance Medan, amounting to 803 customers. The number of samples taken was 89 respondents where the number of samples was determined by the Slovin formula. The side technique used was purposive sampling. This research was conducted in 2022. This research used quantitative data processed by SPSS with multiple linear regression models. The results showed that service quality, trust, and company image had a positive and significant effect on customer satisfaction at PT Bima Finance Medan either partially or simultaneously. Service quality was the most dominant variable affecting customer satisfaction with a regression value of 0.462 and tcount of 6.661. 94.0% customer satisfaction can be explained and obtained from service quality, trust, and company image, while the rest was by other factors. Customer satisfaction had a very strong / close relationship to service quality, trust, and company image.Keywords: Service Quality, Trust, Company Image, Customer Satisfaction.